Baicalein Potentiated M1 Macrophage Polarization in Cancer Through Targeting PI3Kγ/ NF-κB Signaling - He, Shan; Wang, Shangshang; Liu, Suqing; Li, Zheng; Liu, Xiao; Wu, Jinfeng (Frontiers in Pharmacology, 2021)
Baicalein is one of the bioactive compounds extracted from Scutellaria baicalensis. Recent studies indicated the antitumor effects of baicalein, however, the underlying mechanisms are needed to be further determined. In this study, we found that baicalein could inhibit the tumor growth in mice models of breast cancer and melanoma and worked as an immunomodulator to promote the infiltration of tumor-associated macrophages (TAMs) and skew the TAMs towards the M1-like phenotype. Baicalein also induced M1-like phenotype polarization in THP-1-derived macrophages. Meanwhile, the expression of pro-inflammatory factors associated with M1 macrophages, including TNF-α, IL-1β, CXCL9 and CXCL10, were increased after baicalein treatment. Mechanistically, the RNA-seq data suggested that baicalein potentiated the M1 macrophage polarization via the NF-κB/TNF-α signaling pathway. ELISA and confocal microscopy assay confirmed that baicalein significantly induced the production of TNF-α and the activation of NF-κB, while TNF-α neutralization inhibited baicalein-induced macrophage polarization toward M1, and NF-κB P65 knock-down suppressed baicalein-induced TNF-α production in THP-1-derived macrophages. Phosphoinositide 3-kinase (PI3k) γ has been reported as a key molecule in macrophage polarization, and inhibition of PI3Kγ activates the NF-κB-related inflammatory signals. Our pharmacological network analysis predicted that PI3Kγ might be one of the major targets of baicalein. The results from the docking program and surface plasmon resonance (SPR) confirmed that baicalein displayed good binding activity to PI3Kγ. We further found that baicalein not only exhibited a direct inhibitory effect on the protein kinase activity of PI3Kγ, but also reduced the mRNA and protein expression of PI3Kγ, indicating that baicalein might be a novel PI3Kγ inhibitor. In summary, baicalein mediated the TAMs skewing to M1-TAMs, and then retarded tumor growth. These effects, at least in part, were linked to the PI3Kγ/NF-κB signaling.